2023
DOI: 10.1111/cfs.13006
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between adverse childhood experiences, health and life satisfaction in adults with care experience: The mediating role of attachment

Abstract: Adverse childhood experiences (ACEs) are associated with a plethora of negative outcomes. Research has also found that adults who were separated from parental care and lived in alternative care settings during childhood have high levels of ACEs and are more likely to have poor outcomes. A growing body of research has supported the importance of attachment as a mechanism underlying the relationship between ACEs and adult wellbeing. However, little work has examined the role that attachment may play in the outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Establishing evidence reveals a significant relationship between insecure attachment style and mental health problems. A recent study with 529 adults with ACEs showed that participants who scored high in anxious and avoidant attachment were more likely to show mental health problems (Howard, Gwenzi, Taylor, & Wilke, 2023). A longitudinal study with 154 women with history of ACEs revealed that the insecure attachment predicted the major depression and anxiety disorders (Bifulco et al, 2006).…”
Section: Attachment Theory As a Lens Of Understanding The Aces And Su...mentioning
confidence: 99%
“…Establishing evidence reveals a significant relationship between insecure attachment style and mental health problems. A recent study with 529 adults with ACEs showed that participants who scored high in anxious and avoidant attachment were more likely to show mental health problems (Howard, Gwenzi, Taylor, & Wilke, 2023). A longitudinal study with 154 women with history of ACEs revealed that the insecure attachment predicted the major depression and anxiety disorders (Bifulco et al, 2006).…”
Section: Attachment Theory As a Lens Of Understanding The Aces And Su...mentioning
confidence: 99%
“…Young adults who experienced separation from parental care during childhood are more likely to experience negative outcomes in adulthood including a higher risk of self-harm [ 17 ], violent criminal behavior [ 18 ], and homelessness [ 19 ]. Previous studies have also shown evidence of poor mental health, lower life satisfaction, insecure attachment, and less resilience among young adults with care experience due to their limited social connections [ 12 , 20 , 21 ]. Specifically, adults with care experience have been documented to experience challenges during emerging adulthood due to strained relationships with their biological families [ 22 ], poor social networks [ 16 ], and lack of social capital and resources [ 10 , 23 ].…”
Section: Introductionmentioning
confidence: 99%